Grace Reed’s Superiority Over Samantha Reef in Huntley Fitzpatrick’s “My Life Next Door” - Marsyadiah, Midna Nur (LANTERN (Journal on English Language, Culture and Literature), 2016)
This extended essay tries to analyze superiority complex from the character of Grace Reed in Huntley Fitzpatrick’s novel My Life Next Door. In writing this paper, the writer uses library researc that is done by reading books, articles, or any written visual documents related to the topics. While in answering questions, the writer tries to analyze intrinsic aspect and extrinsic aspect with Alfred Adler’s individual psychology theory about superiority and inferiority complex. The purpose of this study is to show the kinds of Grace Reed’s superiority over Samantha Reed, the causes on why superiority is exist in Grace Reed’s character and to the effects of Grace’s Reed superiority towards Samantha Reed. The result show that Grace Reed’s superiority can be seen from how Grace Reed behave in everyday life, the factors from the circumstances and the conflicts that happened to the character